Preclinical evaluation of multi stimuli responsive core-plasmonic nanoshell for photo-triggered tumor ablation: A disintegrable nanohybrid. (September 2020) - Reddy, B. Pradeep K.; Mishra, Sumit K.; Ravichandran, Gayathri; Chauhan, Deepak S.; Srivastava, Rohit; De, Abhijit
Highlights: Preparation of gold modified dual responsive chitosan-g-PNVCL core-gold nanoshell, and scale-up Demonstration of immunocompatibility, hemocompatibility and storage stability Photothermal efficacy testing in breast tumor mice model, and comparison of dose dependent efficacy Demonstration of disintegrable nature of nanoshell upon 750 nm laser irradiation, and efficient renal clearance Abstract: Photothermal therapy (PTT) has gained tremendous interest as a mode of localized cancer therapy. Herein, we report a stable NIR absorbing gold modified dual responsive polymer core, chitosan-g-PNVCL (Au PNVCL NS). The in vitro studies reveal that Au PNVCL NS is a thermo-labile, non-immunogenic, biocompatible material possessing excellent photothermal transduction potential. The acute single-dose toxicity testing in mice reveals no abnormalities, indicating good tolerability of formulation. Au PNVCL NS shows excellent tumor ablation efficacy in vivo upon irradiation with 750 nm laser, thus improving the disease-free longevity of mice. Importantly, keeping our focus on the fate of this material, a significant surge of gold nanoparticles of size ~5 nm in the urine samples of treated mice assures rapid elimination of the material soon after PTT. These results, along with numerous gold nanoparticles deposition in the kidney of mice receiving PTT affirms the disintegrable nature of this nanoformulation while maintaining the desired PTT efficacy. Graphical abstract: Image, graphical abstract